Approximation for absolutely continuous functions by Stancu Beta operators - Zeng, Xiao Ming (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In this paper, we obtain an exact estimate for the first-order absolute moment of Stancu Beta operators by means of the Stirling formula and integral operations. Then we use this estimate for establishing a theorem on approximation of absolutely continuous functions by Stancu Beta operators.